Hydrogen production by steam reforming of ethanol over nickel catalysts supported on sol gel made alumina: influence of calcination temperature on supports - Yaakob, Zahira; Bshish, Ahmed M.; Ebshish, Ali; Tasirin, Siti Masrinda; Alhasan, Fatah H. (MDPI, 2013)
Selecting a proper support in the catalyst system plays an important role in hydrogen production via ethanol steam reforming. In this study, sol gel made alumina supports prepared for nickel (Ni) catalysts were calcined at different temperatures. A series of (Ni/AlS.G.) catalysts were synthesized by an impregnation procedure. The influence of varying the calcination temperature of the sol gel made supports on catalyst activity was tested in ethanol reforming reaction. The characteristics of the sol gel alumina supports and Ni catalysts were affected by the calcination temperature of the supports. The structure of the sol gel made alumina supports was transformed in the order of γ → (γ + θ) → θ-alumina as the calcination temperature of the supports increased from 600 °C to 1000 °C. Both hydrogen yield and ethanol conversion presented a volcano-shaped behavior with maximum values of 4.3 mol/mol ethanol fed and 99.5%, respectively. The optimum values were exhibited over Ni/AlS.G800 (Ni catalyst supported on sol gel made alumina calcined at 800 °C). The high performance of the Ni/AlS.G800 catalyst may be attributed to the strong interaction of Ni species and sol gel made alumina which lead to high nickel dispersion and small particle size.